Evaluation of the techno-economic performance of battery electric buses: Case study of a bus line in paris. (November 2022) - Basma, Hussein; Haddad, Marc; Mansour, Charbel; Nemer, Maroun; Stabat, Pascal
Abstract: The high cost of battery electric buses (BEB), driven by battery and infrastructure costs, is a key factor limiting their market penetration. These costs are determined by the choice of battery size and charging infrastructure. In addition, the electrification of public transit buses raises questions regarding the fleets' punctuality toward their pre-defined schedules, due to the possible schedule delays resulting from BEB charging. In this context, this paper presents a methodology to assess the techno-economic performance of BEB fleets for different battery sizes and charging infrastructures and strategies. The proposed methodology is based on a detailed total cost of ownership (TCO) model considering purchase, operation, maintenance, and infrastructure costs. In addition, a punctuality index (PI) is introduced to quantify schedule delays due to BEB charging events during the day. A case study is used to illustrate the model and results show that overnight charging has the highest TCO, 13% higher than the TCO observed during end-line or opportunity charging. Moreover, a clear trade-off is observed between TCO and BEB punctuality to their schedule. Results show that there is significant room to reduce the TCO of BEB while respecting their operational constraints, by co-optimizing the battery size and charging infrastructure.